Islamic Science and Engineering - Hill, Donald R. (The New Edinburgh Islamic Surveys : NEIS, 2022)
This introduction to the physical sciences and engineering of the Islamic world is the first to trace the full extent of the Muslim scientific achievement in the period 750-1500. It describes how Muslim scientists and engineers contributed enormously to the technology of medieval Europe